2019
DOI: 10.3847/1538-4357/aaf9a0
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Afterglows of Short Gamma-Ray Bursts: Magnetar or Fireball?

Abstract: The origin of the X-ray afterglows of gamma-ray bursts has regularly been debated. We fit both the fireball-shock and millisecond-magnetar models of gamma-ray bursts to the X-ray data of GRB 130603B and 140903A. We use Bayesian model selection to answer the question of which model best explains the data. This is dependent on the maximum allowed non-rotating neutron star mass M TOV , which depends solely on the unknown nuclear equation of state. We show that the data for GRB140903A favours the millisecond-magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…(12) with (µ 1 , σ 1 ) = (1.32, 0.11), (µ 2 , σ 2 ) = (1.80, 0.21), and let be a free parameter which we infer through our hierarchical model. Following Sarin et al [20], one can derive the post-merger remnant mass distribution having the same functional form as Eq. (12) with (µ 1 , σ 1 ) = (2.42, 0.09), (µ 2 , σ 2 ) = (3.21, 0.25) assuming ≈ 0.07M of dynamical ejecta is produced in the merger, consistent with observations of GW170817 [e.g., 49].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(12) with (µ 1 , σ 1 ) = (1.32, 0.11), (µ 2 , σ 2 ) = (1.80, 0.21), and let be a free parameter which we infer through our hierarchical model. Following Sarin et al [20], one can derive the post-merger remnant mass distribution having the same functional form as Eq. (12) with (µ 1 , σ 1 ) = (2.42, 0.09), (µ 2 , σ 2 ) = (3.21, 0.25) assuming ≈ 0.07M of dynamical ejecta is produced in the merger, consistent with observations of GW170817 [e.g., 49].…”
Section: Methodsmentioning
confidence: 99%
“…Although a sharp drop in luminosity cannot be adequately explained within the fireball-shock model, we perform Bayesian model selection between our collapsing magnetar model and an agnostic fireball-shock model as described in [20] to ensure the data is best explained by a collapsing magnetar model. The Bayes factors comparing the fireball-shock and magnetar model for these 18 gamma-ray bursts are shown in Table II likely 1 , the collapsing magnetar model is significantly favoured over the fireball-shock model indicating that the X-ray afterglow observations here are best explained by the presence of a long-lived neutron star which collapses at some time.…”
Section: Neutron Star Collapse Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both fireball models and central engine models are capable of explaining some (but not all) features of X-ray plateaux. Sarin et al (2019) demonstrated that GRB140903A and GRB130603B favour a simple magnetar model, making these two sGRBs particularly suited to investigating the plerion-inspired model in this paper.…”
Section: Introductionmentioning
confidence: 85%
“…Due to the complexity of the coalescence stages, i.e., inspiralling, merging, and ringdown, multi-stage measurements have been made for some SGRBs, including precursor flares, main episodes, and afterglows. Each delivers different information on NS physics, such as the equation of state (EOS) and the central engine of emissions from both the progenitors (Giacomazzo et al 2013;Ascenzi et al 2019) and the remnants (Lasky et al 2014;Sarin, Lasky, & Ashton 2019;Suvorov & Kokkotas 2020b). In particular, precursor flares have been observed for a few SGRBs with some of them likely occuring before the merger (Tsang et al 2012).…”
Section: Introductionmentioning
confidence: 99%